2020
DOI: 10.3389/fenrg.2020.00181
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural Changes of Lignin Macromolecules From Balsa Wood at Different Growth Stages

Abstract: Lignin is the most abundant aromatic biomacromolecule on the earth, which is an attractive raw material for producing bio-based chemicals, materials, and fuels. However, the complexity, heterogeneity, and variability of the lignin structure always hinders the value-added application of different sources of raw materials. In this study, double enzymatic lignin (DEL) was isolated from balsa grown for different lengths of time to understand the structural variations of lignin macromolecules during the growth of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The acquisition time was increased from 200 ms to 30 s to improve the signal-to-noise ratio. The information obtained from the point PiFM spectra mostly confirmed the observations from the hyPIR experiments: high lignin content and presence of condensed lignin structures in CCML and CML (Agarwal 2006;Burke et al 1974;Meier 1985;Whiting and Goring 1983;Zhang et al 2020) and axially oriented EFs in S 2 (Fig. 5).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The acquisition time was increased from 200 ms to 30 s to improve the signal-to-noise ratio. The information obtained from the point PiFM spectra mostly confirmed the observations from the hyPIR experiments: high lignin content and presence of condensed lignin structures in CCML and CML (Agarwal 2006;Burke et al 1974;Meier 1985;Whiting and Goring 1983;Zhang et al 2020) and axially oriented EFs in S 2 (Fig. 5).…”
Section: Resultssupporting
confidence: 80%
“…The softwood lignin is of the guaiacyl type, formed mostly through oxidative polymerization of coniferyl alcohol (Jingjing 2011). The lignin content of wood is highest in CCML and CML (Zhang et al 2020). In these regions, the lignin is more condensed or cross-linked in comparison with the secondary wall lignin.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, we found that native lignin samples from some fast-growing lignocellulosic biomasses were rich in β-O-4 aryl ether linkages, and these lignin fractions have a linear molecular structure. 24,25 For example, the native lignin from bamboo ( Phyllostachys pubescens ) parenchyma cells was rich in Syringyl (S-type) lignin units and β-O-4 linkages. 26 Furthermore, C-lignin, which is naturally abundant in the seed coats of some plant species, has been found to be essentially a homopolymer, synthesized almost entirely from caffeine in combination with growing polymer chains.…”
Section: Lignin As Precursor For Cfs Fabricationmentioning
confidence: 99%
“…The NMR experiment was performed on a Bruker AVIII 400 MHz spectrometer as described [ 15 , 46 , 47 ]. The stem powders were incubated in acetate buffer (0.05 mM, 250 mL, pH = 4.8) with the loading of 6.0 mL Cel-lic ® CTec2 (100 filter paper activity mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to lignin content, the structure and the linkages type of lignin monomers, are also considered as the key factors determining the enzymatic hydrolysis of lignocellulose [10][11][12][13]. In general, higher S or S/G ratio is accompanied with a higher proportion of β-O-4 linkages, which facilitate subsequent depolymerization and enzymatic saccharification [14,15].…”
Section: Biotechnology For Biofuels and Bioproductsmentioning
confidence: 99%